2014
DOI: 10.1128/iai.01500-13
|View full text |Cite
|
Sign up to set email alerts
|

CD8+T Cells Eliminate Liver-Stage Plasmodium berghei Parasites without Detectable Bystander Effect

Abstract: bImmunization with attenuated Plasmodium sporozoites or viral vectored vaccines can induce protective CD8 ؉ T cells that can find and eliminate liver-stage malaria parasites. A key question is whether CD8 ؉ T cells must recognize and eliminate each parasite in the liver or whether bystander killing can occur. To test this, we transferred antigen-specific effector CD8؉ T cells to mice that were then coinfected with two Plasmodium berghei strains, only one of which could be recognized directly by the transferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 34 publications
2
53
0
Order By: Relevance
“…Previous studies from our group and others have shown that CD8 + T cells induced by whole parasites are capable of killing Plasmodium-infected hepatocytes in vitro and in vivo (18,30,31). In this study, we determined that ITV-induced liver CD8 + T cells are also capable of interfering with the development of malariainfected hepatocytes in vitro (Fig.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Previous studies from our group and others have shown that CD8 + T cells induced by whole parasites are capable of killing Plasmodium-infected hepatocytes in vitro and in vivo (18,30,31). In this study, we determined that ITV-induced liver CD8 + T cells are also capable of interfering with the development of malariainfected hepatocytes in vitro (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…4). Several mechanisms have been implicated in the killing of infected hepatocytes by CD8 + T cells, including the production of proinflammatory cytokines such as IFN-g and TNF-a, the production of cytotoxic molecules such as perforin and granzyme, and the clustering of CD8 + T cells around infected hepatocytes (18,31,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, animal model studies using whole-parasite vaccines have shown that gamma interferon-positive (IFN-␥ ϩ ) CD8 ϩ T cells are essential for protection of mice against sporozoite challenge and that protection is likely mediated by direct killing of parasite-infected hepatocytes (4)(5)(6)(7)(8)(9)(10). These findings agree with human clinical trial data showing that the level of sporozoite-specific T cells elicited by immunization with wholeparasite malaria vaccines correlates with protection (11)(12)(13)(14).…”
supporting
confidence: 81%
“…1C). Hence, on the basis of phenotypic expression, immunization of TAP −/− mice with P. berghei RAS did not cause a significant differentiation of CD8 + T cells into CD8 + T EM cells.To resolve whether liver CD8 + T cells from P. berghei RAS immunized mice in both groups represent mainly Ag-specific populations rather than bystander CD8 + T cells [42] recruited by an inflammatory milieu, we adoptively transferred TCR Tg CD8 + T cells specific for the SIINFEKL OVA peptide from OT-1 mice to WT and TAP −/− mice prior to immunization with P. berghei RAS or OVA/Poly (I:C). OT-1 cells expanded in both WT and TAP −/− mice upon immunization with OVA/Poly(I:C), but did not expand in either WT or TAP −/− mice immunized with 75000 P. berghei RAS ( Fig.…”
mentioning
confidence: 99%